(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
The article is about engineering geological classification of white soils. The nature of structural bonds are in classification principles: white soils with hard structural bonds (rocky, semi-rocky soils) and white soils without hard bonds (disperse soils). According to the results of geotechnical investigations of white soils besides classification, characteristic features of white soils engineering geological properties (subsidence, salinity, suffosion etc.) are also brought.